The Influence of Learning Communication on Understanding Pancasila Material to Strengthen National Insight of Class VIII Students of SMP Negeri 1 Bilah Hulu - Silaban, Andika; Junita, Junita; Anjar, Agus (Lembaga Riset Mutiara Akbar, 2024)
The aim of this research is to determine: The influence of learning communication on understanding Pancasila material to strengthen the national insight of class VIII students at SMP Negeri 1 Bilah Hulu. The population in this study were all Class VIII students at SMP Negeri 1 Bilah Hulu. totaling 283 people. The number of samples taken was 74 students as respondents. This research uses an associative-quantitative approach with a simple linear regression model. Data collection was carried out by distributing questionnaires. Research data was processed using SPSS 22.0. The results of the research show that: Learning Communication (X) partially has a positive and significant effect on the understanding of Pancasila material for strengthening the national insight of class VIII students at SMP Negeri 1 Bilah Hulu. Based on the calculations, the linear regression coefficient value for the Learning Communication variable (X) is 0.379, with a positive sign at sig 0.001, which is smaller than 0.05, namely 0.001 < 0.05. So, it can be interpreted that Learning Communication (X) has a positive and significant effect on the understanding of Pancasila material for strengthening the national insight of class VIII students at SMP Negeri 1 Bilah Hulu.